A case series on immunotherapy for leprosy reactions - Thakur, Manjula; Mohankar, Atul Dilip; Swain, Jyoti Prakash (International Journal Of Community Medicine And Public Health, 2024)
Leprosy is a chronic granulomatous disease caused by mycobacterium leprae. As a result of immunological alterations evoked by organism, patients suffer from acute inflammatory episodes known as leprosy reactions, which can continue to occur before, during and after stoppage of therapy and are a cause of concern for the resulting morbidity. Understanding the beneficial effects of immunotherapy with chemotherapy will help in reducing reactions as well the duration of treatment. Five untreated patients of middle age with MI=0 was enrolled in our study who were presented with lepra reactions started on Multi-drug therapy (MDT) and then sent for BCG vaccination. Patients were evaluated monthly for clinical improvement 60% of patients showed improvement within 3 to 4 months whereas 40% patient showed improvement in 7 to 8 months of immunotherapy. Despite of available effective MDT, persisting viable organisms as well as persisting clinical activity are significant problems in leprosy patients. Immunotherapy combined with chemotherapy is good and more promising options to overcome these problems.